1998
DOI: 10.1080/00305316.1998.10433775
|View full text |Cite
|
Sign up to set email alerts
|

The Indian species ofHomalotylus(Hymenoptera : Encyrtidae)

Abstract: The Indian species of the encyrtid genus Homalotylus Mayr are revised. Twelve species are recognized as valid. including two species described as new. Three species are recorded for the first time from India. and four specific names are placed in synonymy. Also a key is given for identification of the species. The tribes Homalotylini. Echthroplexiellii and Brethesiellii are placed in synonymy with Aphycini.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…T7 of gaster relatively longer, cercal plates situated at about distal third of gaster. External genitalia with a tubular phallobase, with aedeagal apodemes contained within the phallobase; parameres absent or reduced; digiti well developed, each digitus usually with three denticles (Anis and Hayat 1998).…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…T7 of gaster relatively longer, cercal plates situated at about distal third of gaster. External genitalia with a tubular phallobase, with aedeagal apodemes contained within the phallobase; parameres absent or reduced; digiti well developed, each digitus usually with three denticles (Anis and Hayat 1998).…”
Section: Diagnosismentioning
confidence: 99%
“…Further, he reported that 30 species were reared from grubs and pupae of ladybirds. Anis and Hayat (1998) added that the hosts of Homalotylus are definitely lady bird beetles, and host records of mealy bugs and aphids are undoubtedly erroneous and indicate that the real hosts, which normally live among these hemipterous pests, are overlooked. Sixty-four species of Homalotylus have been described globally (Noyes 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 It makes either solitary or gregarious parasitism to lady beetle larvae and young pupae. [28][29][30] A preliminary observation on its parasitism of C. septempunctata larvae suggests that intermediate instar larvae are of higher quality than younger and older larvae for the offspring development. 16 This developmental trait is in line with the 'domed fitness functions' performed often by koinobiont parasitoids and host caterpillars.…”
Section: Introductionmentioning
confidence: 99%
“…Homalotylus species can cause a decrease in lady beetle populations (Anis and Hayat 1998;Ceryngier et al 2012). High rates of parasitism (90-95%) reported in several studies indicate they may limit the efficacy of entomophagous coccinellids (Hodek 1973;Kenis et al 2008).…”
mentioning
confidence: 99%